Wave-induced morphodynamics and sediment transport around a slender vertical cylinder. (July 2019) - Miozzi, Massimo; Corvaro, Sara; Alves Pereira, Francisco; Brocchini, Maurizio
Abstract: We study the dynamics of a sandy bed around a slender vertical cylinder forced by progressive, non-linear water waves. The seabed evolves continuously under the effects of the up-welling, down-welling and rolling events induced by vortical coherent structures. In turn, these are closely connected to the shape of the seabed, which is modified by the scouring and/or the deposition of the sand. Starting from a flat seabed, progressive waves induce a rapid and transient modification of the bottom morphology towards a dynamically stable equilibrium state, which is the focus of this work. The dynamical equilibrium state is a function of the wave period and is reached when the seabed morphology is not substantially altered. We describe such a state by an Eulerian in-phase analysis of the sand particle motion, inferred from Lagrangian data collected over a large number of wave passages. This analysis relies on the use of the defocusing digital PIV technique (DDPIV), for the first time applied to the specific flow of interest here. On the basis of the Eulerian analysis, the triggering of the key-events (up- and down-welling, rolling) over the wave phase is captured by identifying, through the Q  > 0 criterion, the coherent flow structures responsible for the events. This analysis is coupled with the description of the sediment trajectories, analyzed in a Lagrangian manner and effectively assessing how and where the solid phase is transported during the key-events. Five main mobilization/transport mechanisms have been identified, three during the onshore flow and two during the offshore flow: (i) generation of a coherent structure reminiscent of a horseshoe vortex at the toe, (ii) intense scouring at the top of the flatbed region, (iii) vortex shedding in the wake during direct (onshore) flow, (iv) shear crossflow on the lee-side of the cylinder and (v) large vertical shearing in the flatbed region during the reverse (offshore) flow. At flow reversal, this shearing mechanism impacts on a significant area of sediments in the incoming region of the flow.